Risk-based decision-support tool for prevention and control of Rift Valley fever epizootics in the Greater Horn of Africa - International Livestock Research Institute; Food and Agriculture Organization of the United Nations (International Livestock Research Institute, 2010)
Following the 2006/07 Rift Valley fever (RVF) epizootic in East Africa, a participatory assessment carried out jointly by the International Livestock Research Institute (ILRI) and the Government of Kenya Department of Veterinary Services (GoK DVS) concluded that: “The severity of the...RVF epidemic in northern Kenya was exacerbated by delays in recognizing risk factors...and in taking decisions to prevent and control the disease.” Further, it noted that “Kenya lacks a well documented contingency/emergency plan for RVF.” Amongst factors which limited the response to the outbreak, the assessment highlighted the “lack of pre-allocated emergency funds, particularly within the livestock sector” which greatly delayed responses (ILRI 2008).